Different factors drive the assembly of pine and Panax notoginseng-associated microbiomes in Panax notoginseng-pine agroforestry systems - Jia, Weijia; Wang, Shu; He, Xiahong; Zhao, Xiaoyan (Frontiers in Microbiology, 2022)
Land-use conversion affects the composition and assembly of plant-associated microbiomes, which in turn affects plant growth, development, and ecosystem functioning. However, agroforestry systems, as sustainable land types, have received little attention regarding the dynamics of different plant-associated microbes. In this study, we used high-throughput sequencing technology to analyze the assembly mechanisms and the driving factors of pine- and Panax notoginseng (P.n.)-associated microbiomes during the conversion of different pine forests (Pinus kesiya var. langbianensis and Pinus armandii) into P.n.-pine agroforestry systems. The results showed that the conversion of pure pine forest into P.n.-pine agroforestry systems significantly altered the diversity of pine-associated fungi rather than the community structure, and the community structure of P.n.-associated fungi rather than the diversity. Additionally, plant-associated fungi were more responsive to land-use change than bacteria. Main effect analysis revealed that compartment rather than genotype was the driving factor of pine- and P.n.-associated microbiomes, but P.n. cultivation also significantly affected the assembly of pine-associated microbiomes. In addition, there was a transfer of P.n. endophytes to pine trees in agroforestry systems and the beneficial microbiomes (Massilia, Marmoricola, Herbaspirillum, etc.) were enlarged in pine roots. Therefore, the diversity of the assembly mechanisms of P.n.- and pine-associated microbiomes played an important role in the P.n.–pine agroforestry systems and were the basis for the sustainable development of the P.n.–pine agroforestry systems.